Which values do today's youth believe in? The values and ideal models of 280 students from some Italian schools - Sara Guirado (Firenze University Press, 2022)
Our society doesn't always give space to young people. Generational renewal is not seen as an opportunity and is therefore often hampered by short-sighted political decisions. Consequently, a generalized crystallization is created that inevitably puts at a disadvantage those who have yet to build a future for themselves. The article proposes a series of reflections supported by updated data extracted from sociological and statistical research and from the research carried out for the master's thesis in Philosophy of Education that demonstrate how, despite the difficulties and obstacles of our time, nowadays young people they have a wealth of values. The instrument used is a questionnaire and the general objective is to implement pedagogical knowledge on the subject of values ​​in relation to young people. The context analyzed is Italian and in particular the research of which I present some results was carried out in the city of Pistoia. Keywords: Philosophy of Education, youth condition, values, liquid society, generational change.